On the measurement of hedging effectiveness for long-term investment guarantees - Maciej Augustyniak; Alexandru Badescu; Mathieu Boudreault (Journal of Risk and Financial Management, 2023)
Although the finance literature has devoted a lot of research into the development of advanced models for improving the pricing and hedging performance, there has been much less emphasis on approaches to measure dynamic hedging effectiveness. This article discusses a statistical framework based on regression analysis to measure the effectiveness of dynamic hedges for long-term investment guarantees. The importance of taking model risk into account is emphasized. The difficulties in reducing hedging risk to an appropriately low level lead us to propose a new perspective on hedging, and recognize it as a tool to modify the risk-reward relationship of the unhedged position.
Keywords: 650; dynamic hedging; hedging effectiveness; investment guarantee; model risk; variable annuity